Judging gymnastics with biomechanics - Sands, W. A.; McNeal, J. R.
Human judges often have difficulty in determining the subtle differences in trajectories and speed between competitors in gymnastics. We have devised an objective scoring system for the compulsory vault by using video digitizing, infrared timers, and a computer algorithm. We combined the objective score with a human judge's score for form errors. The objective score successfully increased the differentiation between performances in a trial of 25 gymnasts at a competition.